Understanding lay-public perceptions of energy storage technologies: Preliminary results of a questionnaire conducted in Canada. (May 2020) - Gaede, James; Jones, Christopher R.; Ganowski, Sara; Rowlands, Ian H.
Abstract: 'Grid-scale' energy storage technologies (ESTs) provide energy storage at scales, capacity and power levels necessary to support the operation of electricity grids, particularly those with substantial renewable (e.g., wind and solar) generation capacity. Public perceptions of new and innovative technologies are known to influence their commercial success, yet there is little existing literature into perceptions and antecedents of grid-scale electricity storage among the general public. In this paper, we report on the findings of an online survey distributed to a diverse sample of the Canadian public ( N = 1, 022), focusing on perceptions of four specific ESTs (i.e., compressed air energy storage, flywheels, lithium ion batteries, and pumped hydro storage) and the factors that influence intentions to accept ESTs. This research is part of a larger joint-project between researchers at the University of Waterloo and the University of Surrey designed to investigate the similarities and differences in public perceptions of grid-scale ESTs in Canada and the UK. This paper compliments an earlier one that presented the findings for the same survey conducted on a diverse sample of the UK public.